#### Answer

(-$\frac{1}{4}$, 2)

#### Work Step by Step

Write the first equation as a solution for x:
x = $\frac{5}{12} - \frac{1}{3}y$
Insert the equation for x in terms of y in the second equation:
8($\frac{5}{12} - \frac{1}{3}y$) + 3y = 4
$\frac{10}{3} - \frac{8}{3}y$ + 3y = 4
$\frac{10}{3} + \frac{1}{3}y$ = 4
$\frac{1}{3}y = \frac{2}{3}$
y = 2
Let y = 2 in the first equation to solve for y:
x + ($\frac{1}{3})2 = \frac{5}{12}$
x = $\frac{5}{12} - \frac{2}{3}$
x = -$\frac{3}{12}$
x = -$\frac{1}{4}$
Check the solution (-$\frac{1}{4}$, 2) in the second equation:
8(-$\frac{1}{4}$) + 3(2) = 4
-2 + 6 = 4
4 = 4; True